The impact of COVID-19 lockdown on the quality of life of Chinese football referees: the chain mediating role of occupational stress and job burnout - Xianliang Wang; Kehao Zong; Yubo Gao; Bochen Li; Shuzhen Wang; Liguo Zhang (BMC, 2023)
Abstract Background COVID-19 lockdown measures have had a great negative impact on the development of sports competition in China, as well as on the quality of life of football referees. This study aims to explore the impact of lockdown measures implemented in response to the COVID-19 pandemic on the quality of life of football referees in China and its mechanism of action. Methods The Impact of Event Scale-Revised (IES-R), the Effort-Reward Imbalance Scale (ERI), the Maslach Burnout Inventory General Survey (MBI-GS), and the World Health Organization Quality of Life Brief Version (WHOQOL-BREF). The scale was used from August to September 2022. Using an online questionnaire, 350 questionnaires were sent out and 338 were returned, for a return rate of 96.57%. Invalid questionnaires were excluded, and 307 football referees with referee grades in 29 provinces registered with the CFA were surveyed. SPSS 24.0 and Mplus 8.0 were used for data analysis and structural equation model testing in this study. Results The results showed that the COVID-19 lockdown had no significant impact on the quality of life of Chinese football referees. However, the COVID-19 lockdown can affect the quality of life of Chinese football referees through occupational stress or job burnout. Occupational stress and job burnout also play a chain intermediary role between the COVID-19 lockdown and the quality of life of Chinese football referees. In addition, this study further explores the quality of life by dividing it into four dimensions (physical, social, psychological, and environmental). The results show that all four dimensions satisfy the chain mediation model. Conclusions Therefore, the quality of life of Chinese football referees can be improved by reducing their occupational stress and job burnout during the COVID-19 lockdown.